2011
DOI: 10.1093/cid/ciq188
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Excess and Periostitis in Transplant Patients Receiving Long-Term Voriconazole Therapy

Abstract: Voriconazole is associated with painful periostitis, exostoses, and fluoride excess in post-transplant patients with long-term voriconazole use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
151
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(167 citation statements)
references
References 22 publications
7
151
4
Order By: Relevance
“…As seen in this case, and described elsewhere, fluoride levels persist after withdrawal of voriconazole, despite symptom resolution, 3,6 which suggests that the fluoride is sequestered in, and slowly released from, the skeleton. It has been suggested that intermittent treatment with recombinant parathyroid hormone (teriparatide) to increase bone turnover might assist with removal of skeletal fluoride 11 ; however, the need for such treatment in the absence of symptoms is unclear.…”
Section: Discussionsupporting
confidence: 81%
“…As seen in this case, and described elsewhere, fluoride levels persist after withdrawal of voriconazole, despite symptom resolution, 3,6 which suggests that the fluoride is sequestered in, and slowly released from, the skeleton. It has been suggested that intermittent treatment with recombinant parathyroid hormone (teriparatide) to increase bone turnover might assist with removal of skeletal fluoride 11 ; however, the need for such treatment in the absence of symptoms is unclear.…”
Section: Discussionsupporting
confidence: 81%
“…Concerns regarding the potential toxicity of long-term triazole therapy have been raised, and recent observations have presented compelling evidence for the causal role of long-term voriconazole, a trifluorinated antifungal, as a risk factor for the development of fluoride excess and subsequent painful periostitis and exostoses in posttransplant patients (1,2,5). However, the safety and potential toxicity of fluconazole and posaconazole (difluorinated triazoles) have not been assessed, nor has hyperfluorosis been reported for nontransplant patients.…”
mentioning
confidence: 99%
“…Fluoride is a major component of this antifungal, and is central in the pathophysiology of VIPD through stimulation of osteoblasts. 1 Classically VIPD presents with diffuse bony pain and swelling, elevated serum ALP and fluoride levels, dense periosteal reaction on radiographs, as well as multiple areas of uptake on bone scintigraphy. 2,3 Despite the aforementioned abnormalities, voriconazole troughs are often within normal limits.…”
Section: Discussionmentioning
confidence: 99%